PENGAWASAN PERIZINAN USAHA WARUNG INTERNET GAME ONLINE OLEH DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KOTA PEKANBARU TAHUN 2019 - Muhammad Miftah Fauzan; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Internet cafe business opportunities in Pekanbaru City have played a major role. Internet cafe business actors run internet cafe operations without having clear operating hours and a number of internet cafes have not yet obtained a business license. Many people are addicted to playing online games, especially teenagers and young children. This of course has disrupted public order and public order. The above explanation encourages the issuance of Pekanbaru City Regional Regulation Number 6 of 2015 concerning the arrangement and control of telecommunications operations, this is aimed at the realization of quality, efficient and positive internet cafe services for the community. A government oversight is needed through the One Stop Service and Investment Agency (DPMPTSP) to check the available permits. This study uses a descriptive qualitative method with an inductive approach and data collection techniques in the form of observation, documentation, and interviews with the Head and the ranks of the Pekanbaru City Investment and One Stop Integrated Service (DPMPTSP) as resource persons. Based on the research conducted, it was concluded that the Supervision of Business Licensing of Online Game Internet Cafes by the Office of Investment and One Stop Integrated Services (DPMPTSP) of Pekanbaru City was carried out in stages, including: Determining the standard form. Carry out direct and indirect supervision, Research on the object of supervision and take corrective action. The inhibiting factors for the implementation of supervision in this research are: Geographical Conditions, Monitoring System, Human Resources and also the participation of business actors. Keyword: Controlling , Direct Controlling, Indirect Controlling, Corrective Action